Arthroscopic Training Resources in Orthopedic Resident Education - Koehler, Ryan; John, Tamara; Lawler, Jeffrey; Moorman, Claude, III; Nicandri, Gregg (The Journal of Knee Surgery, 2015)
The purpose of this study was to determine the frequency of use, perceived effectiveness, and preference for arthroscopic surgical skill training resources. An electronic survey was sent to orthopedics residents, residency program directors, and orthopedic sports medicine attending physicians in the United States. The frequency and perceived effectiveness of 10 types of adjunctive arthroscopic skills training was assessed. Residents and faculty members were asked to rate their confidence in resident ability to perform common arthroscopic procedures. Surveys were completed by 40 of 152 (26.3%) orthopedic residency program directors, 70 of 426 (16.4%) sports medicine faculty, and 235 of 3,170 (7.4%) orthopedic residents. The use of adjunctive methods of training varied from only 9.8% of programs with virtual reality training to 80.5% of programs that used reading of published materials to develop arthroscopic skill. Practice on cadaveric specimens was viewed as the most effective and preferred adjunctive method of training. Residents trained on cadaveric specimens reported increased confidence in their ability to perform arthroscopic procedures. The resources for developing arthroscopic surgical skill vary considerably across orthopedic residency programs in the United States. Adjunctive training methods were perceived to be effective at supplementing traditional training in the operating room.
Keywords: arthroscopy; education; training resources